Replication and transcription on a collision course: eukaryotic regulation mechanisms and implications for DNA stability - Brambati, Alessandra; Colosio, Arianna; Zardoni, Luca; Galanti, Lorenzo; Liberi, Giordano (Frontiers in Genetics, 2015)
DNA replication and transcription are vital cellular processes during which the genetic information is copied into complementary DNA and RNA molecules. Highly complex machineries required for DNA and RNA synthesis compete for the same DNA template, therefore being on a collision course. Unscheduled replication-transcription clashes alter the gene transcription program and generate replication stress, reducing fork speed. Molecular pathways and mechanisms that minimize the conflict between replication and transcription have been extensively characterized in prokaryotic cells and recently identified also in eukaryotes. A pathological outcome of replication-transcription collisions is the formation of stable RNA:DNA hybrids in molecular structures called R-loops. Growing evidence suggests that R-loop accumulation promotes both genetic and epigenetic instability, thus severely affecting genome functionality. In the present review, we summarize the current knowledge related to replication and transcription conflicts in eukaryotes, their consequences on genome instability and the pathways involved in their resolution. These findings are relevant to clarify the molecular basis of cancer and neurodegenerative diseases.